The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/jpc.13860
|View full text |Cite
|
Sign up to set email alerts
|

Surveying social adversity in pregnancy: The antenatal risk burden experienced by Australian women

Abstract: This study reveals the considerable and varied risk burden experienced by Australian women during pregnancy. By understanding where need is greatest and tailoring support accordingly, risk factor assessment provides an opportunity to address equity through health care, ultimately optimising the future developmental outcomes of all children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 18 publications
2
25
0
Order By: Relevance
“…The larger cohort was representative of women seeking maternity care through Australian publicly funded hospitals (~70% of Australian births19) on factors including mode of birth, gestation and birth weight. The proportion of participants at socioeconomic disadvantage was similar to that of another community based study (15.6% vs 17.5%, respectively9), suggesting that socioeconomic disadvantage was appropriately represented in the larger cohort. Social and obstetric characteristics of the sample are reported in table 1.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The larger cohort was representative of women seeking maternity care through Australian publicly funded hospitals (~70% of Australian births19) on factors including mode of birth, gestation and birth weight. The proportion of participants at socioeconomic disadvantage was similar to that of another community based study (15.6% vs 17.5%, respectively9), suggesting that socioeconomic disadvantage was appropriately represented in the larger cohort. Social and obstetric characteristics of the sample are reported in table 1.…”
Section: Resultssupporting
confidence: 77%
“…At 3 months postpartum, mothers completed items relating to their infant’s gender, length of gestation, birth weight and admittance to a neonatal intensive care unit/special care nursery. In line with prior research,9 mothers were categorised as being at socioeconomic disadvantage if they reported two or more of the following factors during pregnancy: not living with a partner, not working or studying, incomplete schooling (<12 years) or smoking during pregnancy. When their child turned 12 months old, mothers completed the Edinburgh Postnatal Depression Scale (EPDS), a 10-item self-report scale, with higher scores indicating more depressive symptoms (scores range from 0 to 30).…”
Section: Methodsmentioning
confidence: 99%
“…18 We used a brief risk factor survey of 10 broad-ranging psychosocial and socioeconomic risk factors for poorer child outcomes developed and piloted for the study, which showed that 2 (17%) or more adverse risk factors identified 61% of women who reported other more sensitive risk factors (eg, alcohol and drug use and domestic violence) in the standard clinical appointment. 32 Eligible women (1) had due dates before October 1, 2014; (2) were <37 weeks' gestation; (3) had sufficient English to complete interviews; (4) had ≥2 of 10 risk factors identified at screening (Supplemental Table 4) 29,32 ; and (5) had home addresses within travel boundaries specified by participating areas. Women were excluded if they (1) were enrolled in an existing Tasmanian NHV program for 15-to 19-year-olds, (2) did not comprehend the recruitment invitation (eg, intellectual disability or insufficient English), (3) had no mechanism for contact (telephone number or e-mail address), or (4) experienced a critical event (eg, termination of pregnancy, stillbirth, or child death).…”
Section: Design and Participantsmentioning
confidence: 99%
“…Indicators of adversity often cluster; whereby children living in families experiencing one type of adversity are more likely to experience others (Goldfeld, D'Abaco, Bryson, Mensah, & Price, 2018;Sabates & Dex, 2015). This cumulative burden is associated with increasingly poor lifelong health outcomes (Chartier, Walker, & Naimark, 2010;Sabates & Dex, 2015).…”
Section: Introductionmentioning
confidence: 99%